PENGARUH PENYAJIAN LAPORAN KEUANGAN DAERAH, AKSESIBILITAS LAPORAN KEUANGAN DAERAH DAN PENGENDALIAN INTERNAL TERHADAP TRANSPARANSI DAN AKUNTABILITAS PENGELOLAANKEUANGAN DAERAH KOTA DUMAI - Mirza Masyhur; Hardi '; Alfiati Silfi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This study aimed to determine the effect of regional financial statement presentation, accessibility of financial statements and internal control areas to transparency and accountability in the management of local financial statements in Dumai city. The population in this research is all working unit of regional government ( SKPD) in Dumai city which totally 34 SKPD. Samples in this study obtained by using purposive sampling method. This study uses multiple regression analysis linear with SPSS version 20.0. This study uses the classical assumption of the normality test, heterokedasity test, auto test correlation, multicollinearity test, as well as for hypothesis testing using t. This study proves that all the independent variables affect the dependent variable with a significant level (α) <0.05 and a coefficient of determination of 83.4%. Indicated that the financial statement presentation area, accessibility of financial statements and internal control areas affect transparency and accountability in the management of local financial statements amounted to 83.4% Dumai city. and 16.6% are other variables that may affect the transparency and accountability in the management of financial statements in Dumai city areas that are not included in this study.Keywords: Financial Statement, Accessibility, Internal Control, Transparency, Accountability.